α7 Nicotinic Acetylcholine Receptor Signaling Modulates Ovine Fetal Brain Astrocytes Transcriptome in Response to Endotoxin - Cao, Mingju; MacDonald, James W.; Liu, Hai L.; Weaver, Molly; Cortes, Marina; Durosier, Lucien D.; Burns, Patrick; Fecteau, Gilles; Desrochers, André; Schulkin, Jay; Antonelli, Marta C.; Bernier, Raphael A.; et al. (Frontiers in Immunology, 2019)
Neuroinflammation in utero may result in lifelong neurological disabilities. Astrocytes play a pivotal role, but the mechanisms are poorly understood. No early postnatal treatment strategies exist to enhance neuroprotective potential of astrocytes. We hypothesized that agonism on α7 nicotinic acetylcholine receptor (α7nAChR) in fetal astrocytes will augment their neuroprotective transcriptome profile, while the antagonistic stimulation of α7nAChR will achieve the opposite. Using an in vivo - in vitro model of developmental programming of neuroinflammation induced by lipopolysaccharide (LPS), we validated this hypothesis in primary fetal sheep astrocytes cultures re-exposed to LPS in the presence of a selective α7nAChR agonist or antagonist. Our RNAseq findings show that a pro-inflammatory astrocyte transcriptome phenotype acquired in vitro by LPS stimulation is reversed with α7nAChR agonistic stimulation. Conversely, antagonistic α7nAChR stimulation potentiates the pro-inflammatory astrocytic transcriptome phenotype. Furthermore, we conduct a secondary transcriptome analysis against the identical α7nAChR experiments in fetal sheep primary microglia cultures and discuss the implications for fetal and postnatal brain development.